Value of DCE-MRI parameters for short-term prognosis of pharyngeal cancer after postoperative radiotherapy - SUN Shengjie; YAO Lidi; LIU Dong (陆军军医大学学报)
Objective‍　‍To investigate the value of dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) parameters in evaluating the short-term prognosis of laryngeal cancer patients after postoperative radiotherapy. Methods‍　‍A case-control study was performed on 127 laryngeal cancer patients admitted to our hospital from January 2021 to December 2023. The patients underwent different tumor treatment followed by radical radiotherapy. According to tumor recurrence or not, they were divided into a recurrence group (n=50) and a non-recurrence group (n=77). DCE-MRI parameters, such as volume transfer constant (Ktrans), rate constant (Kep), and volume fraction of extracellular extravascular space (Ve), and clinical data were compared between the 2 groups. Multivariate logistic regression analysis was used to identify influencing factors for short-term prognosis after radiotherapy. Receiver operating characteristic (ROC) curves were plotted to evaluate the predictive efficacy of DCE-MRI parameters, and the area under the curve (AUC) was calculated. Results‍　‍The recurrence group had significantly larger proportions of positive surgical margins, preoperative maximum lesion diameter ≥4 cm, ulcerative lesions, stages N1~N3, and advanced stages Ⅲ~Ⅳ, and obviously higher Ktrans and Kep values but lower Ve valus than the non-recurrence group (P<0.05). Multivariate logistic regression analysis indicated that positive surgical margins, stages N1~N3, Ktrans, and Kep were independent risk factors for short-term prognosis, while Ve was a protective factor (P<0.05). ROC curve analysis showed that the AUC value of combination of Ktrans, Kep and Ve and of above 5 indicators in predicting short-term prognosis of postoperative radiotherapy for laryngeal cancer was 0.920 (95%CI: 0.858~0.961) and 0.923 (95%CI: 0.862~0.963), respectively. Though the AUC value of combined 3 parameters was significantly higher than that of the single indicator alone (P<0.05), there was no difference in the value between the combination of 3 parameters and the combined application of the 5 indicators. Conclusion‍　‍DCE-MRI parameters Ktrans, Kep, and Ve are closely associated with short-term prognosis of postoperative radiotherapy for laryngeal cancer. Their combination has a good predictive efficacy for the short-term prognosis of the patients.